An investigation into the interrelationship between petrophysical properties of potential gas shale reservoirs from Western Australia - Labani, Mohammad Mahdi (Curtin University, 2014)
An investigation into petrophysical properties of potential gas shales from the Perth and Canning Basins has been performed to understand the interrelationship between shale composition, geochemical properties and pore structural parameters. The following measurements were done on the samples:• Low pressure nitrogen adsorption and mercury porosimetry technique for determination of the pore structural properties,• Gas expansion method for determining the effective porosity,• High pressure methane adsorption for determination of the adsorbed gas capacity.